ANALYSIS OF UINSU COMMUNICATION STUDENTS ON INTRAPERSONAL COMMUNICATION THAT OCCURS IN THE PODHUB YOUTUBE VIDEO JUAN-EVE PODHUB EDITION - Rizki Darmawan; Nailah S. Ramadhani; Afraina Nuraini; Muhammad Haritz Arrasyid; Khairunnisa (Academic Solution Publisher, 2024)
This study aims to analyze intrapersonal communication as presented in a YouTube Podhub episode featuring Juan and Eve. The main focus of the study is to explore the elements of intrapersonal communication that emerge in the podcast and how Communication Studies students at UINSU assess their influence on personal narratives and interpersonal relationships. Using a qualitative approach, this research examines self-reflection, internal conflict, personal perspectives, and the impact of social and cultural influences on the communication between Juan and Eve. Data were collected through observation and content analysis of the selected podcast video, supported by relevant literature. The findings show that the intrapersonal communication portrayed in this podcast plays an important role in creating authentic narratives and enriching interpersonal relationships between the creators and their audience. This study seeks to provide insights into the importance of self-reflection in building effective communication, particularly in the digital era.